Effects of Graphene Oxide Nanosheets in Freshwater Biofilms - Diana Matos; Salomé F. P. Almeida; Paula A. A. P. Marques; Sofia Pinto; Etelvina Figueira (Molecules, 2023)
Graphene oxide (GO) properties make it a promising material for graphene-based applications in areas such as biomedicine, agriculture, and the environment. Thus, its production is expected to increase, reaching hundreds of tons every year. One GO final destination is freshwater bodies, possibly affecting the communities of these systems. To clarify the effect that GO may impose in freshwater communities, a fluvial biofilm scraped from submerged river stones was exposed to a range (0.1 to 20 mg/L) of GO concentrations during 96 h. With this approach, we hypothesized that GO can: (1) cause mechanical damage and morphological changes in cell biofilms; (2) interfere with the absorption of light by biofilms; (3) and generate oxidative stress, causing oxidative damage and inducing biochemical and physiological alterations. Our results showed that GO did not inflict mechanical damage. Instead, a positive effect is proposed, linked to the ability of GO to bind cations and increase the micronutrient availability to biofilms. High concentrations of GO increased photosynthetic pigment (chlorophyll a, b, and c, and carotenoids) content as a strategy to capture the available light more effectively as a response to the shading effect. A significant increase in the enzymatic (SOD and GSTs activity) and low molecular weight (lipids and carotenoids) antioxidant response was observed, that efficiently reduced oxidative stress effects, reducing the level of peroxidation, and preserving membrane integrity. Being complex entities, biofilms are more similar to environmental communities and may provide more accurate information to evaluate the impact of GO in aquatic systems.